Multicenter screening for pre‐eclampsia by maternal factors and biomarkers at 11–13 weeks' gestation: comparison with NICE guidelines and ACOG recommendations. (June 2017) - O'Gorman, N.; Wright, D.; Poon, L. C.; Rolnik, D. L.; Syngelaki, A.; de Alvarado, M.; Carbone, I. F.; Dutemeyer, V.; Fiolna, M.; Frick, A.; Karagiotis, N.; Mastrodima, S.; et al.
ABSTRACT: Objective: To compare the performance of screening for pre‐eclampsia (PE) based on risk factors from medical history, as recommended by NICE and ACOG, with the method proposed by The Fetal Medicine Foundation (FMF), which uses Bayes' theorem to combine the a‐priori risk from maternal factors, derived by a multivariable logistic model, with the results of various combinations of biophysical and biochemical measurements. Methods: This was a prospective multicenter study of screening for PE in 8775 singleton pregnancies at 11–13 weeks' gestation. A previously published FMF algorithm was used for the calculation of patient‐specific risk of PE in each individual. The detection rates (DRs) and false‐positive rates (FPRs) for delivery with PE < 32, < 37 and ≥ 37 weeks were estimated and compared with those derived from application of NICE guidelines and ACOG recommendations. According to NICE, all high‐risk pregnancies should be offered low‐dose aspirin. According to ACOG, use of aspirin should be reserved for women with a history of PE in at least two previous pregnancies or PE requiring delivery < 34 weeks' gestation. Results: In the study population, 239 (2.7%) cases developed PE, of which 17 (0.2%), 59 (0.7%) and 180 (2.1%) developed PE < 32, < 37 and ≥ 37 weeks, respectively. Screening with use of the FMF algorithm based on a combination of maternal factors, mean arterial pressure (MAP), uterine artery pulsatility index (UtA‐PI) and serum placental growth factor (PlGF) detected 100% (95% CI, 80–100%) of PE < 32 weeks, 75% (95% CI, 62–85%) of PE < 37 weeks and 43% (95% CI, 35–50%) of PE ≥ 37 weeks, at a 10.0% FPR. Screening with use of NICE guidelines detected 41% (95% CI, 18–67%) of PE < 32 weeks, 39% (95% CI, 27–53%) of PE < 37 weeks and 34% (95% CI, 27–41%) of PE ≥ 37 weeks, at 10.2% FPR. Screening with use of ACOG recommendations detected 94% (95% CI, 71–100%) of PE < 32 weeks, 90% (95% CI, 79–96%) of PE < 37 weeks and 89% (95% CI, 84–94%) of PE ≥ 37 weeks, at 64.2% FPR. Screening based on the ACOG recommendations for use of aspirin detected 6% (95% CI, 1–27%) of PE < 32 weeks, 5% (95% CI, 2–14%) of PE < 37 weeks and 2% (95% CI, 0.3–5%) of PE ≥ 37 weeks, at 0.2% FPR. Conclusion: Performance of screening for PE at 11–13 weeks' gestation by the FMF algorithm using a combination of maternal factors, MAP, UtA‐PI and PlGF, is by far superior to the methods recommended by NICE and ACOG. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations. This article has been selected for Journal Club. Clickhere to view slides and discussion points.